Continuing education in the Military Police of Alagoas: The relevance of standardizing official writing as a tool for organizational efficiency (Research, Society and Development, 2026)
The current public security context has required police institutions to improve not only operational efficiency but also the organization of their internal processes. In this scenario, continuous professional development plays a relevant role, especially in strengthening competencies related to institutional communication. This study aims to examine the standardization of official writing within the Military Police of Alagoas (PMAL), considering its effects on organizational performance and its relationship with institutional strategic planning. The research adopts a qualitative and descriptive approach, based on literature review and document analysis. The findings indicate that adopting uniform writing criteria contributes to better organization of administrative routines, reduces divergent interpretations, and strengthens institutional management. It is concluded that consolidating these practices, combined with continuous training, represents a relevant element for improving organizational efficiency.